EVALUATION OF THE EFFECTIVENESS OF THE “DRY TUBE” METHOD USING THE PCR METHOD - Zukhra N. Orinbayeva; Nurshod F. Murotov; Mubina D. Davronova (Central Asian Journal of Medicine, 2024)
In recent years, HIV infection and Hepatitis C have been increasingly prevalent among various age groups in Uzbekistan. Consequently, accurate diagnosis of these diseases in laboratory settings, utilizing the most modern methods, has become essential. This article presents findings where samples from 49 HIV-positive and 26 Hepatitis C-positive patients were tested using the “Dry test tube” method, revealing that the sensitivity of the method was 74.8%.